C/EBPβ induces B‐cell acute lymphoblastic leukemia and cooperates with BLNK mutations. Issue 12 (23rd October 2021) - Kurata, Morito; Onishi, Iichiro; Takahara, Tomoko; Yamazaki, Yukari; Ishibashi, Sachiko; Goitsuka, Ryo; Kitamura, Daisuke; Takita, Junko; Hayashi, Yasuhide; Largaesapda, David A; Kitagawa, Masanobu; Nakamura, Takuro
Abstract: BLNK ( BASH/SLP‐65 ) encodes an adaptor protein that plays an important role in B‐cell receptor (BCR) signaling. Loss‐of‐function mutations in this gene are observed in human pre‐B acute lymphoblastic leukemia (ALL), and a subset of Blnk knock‐out (KO) mice develop pre‐B‐ALL. To understand the molecular mechanism of the Blnk mutation‐associated pre‐B‐ALL development, retroviral tagging was applied to KO mice using the Moloney murine leukemia virus (MoMLV). The Blnk mutation that significantly accelerated the onset of MoMLV‐induced leukemia and increased the incidence of pre‐B‐ALL Cebpb was identified as a frequent site of retroviral integration, suggesting that its upregulation cooperates with Blnk mutations. Transgenic expression of the liver‐enriched activator protein ( LAP ) isoform of Cebpb reduced the number of mature B‐lymphocytes in the bone marrow and inhibited differentiation at the pre‐BI stage. Furthermore, LAP expression significantly accelerated leukemogenesis in Blnk KO mice and alone acted as a B‐cell oncogene. Furthermore, an inverse relationship between BLNK and C/EBPβ expression was also noted in human pre‐B‐ALL cases, and the high level of CEBPB expression was associated with short survival periods in patients with BLNK ‐downregulated pre‐B‐ALL. These results indicate the association between the C/EBPβ transcriptional network and BCR signaling in pre‐B‐ALL development and leukemogenesis. This study gives insight into ALL progression and suggests that the BCR/C/EBPβ pathway can be a therapeutic target. Abstract : C/EBPB was identified as a common retroviral integration site by retroviral tagging in Blnk knock‐out mice. B‐cell specific expression of the C/EBPB LAP isoform enhanced differentiation block of pre‐B‐cell and accelerated leukemogenesis of the Blnk mutation.